SOCIALLY INFLUENTIAL FACTORS OF THE DEVELOPMENT OF SOCIALLY ACTIVE CITIZENSHIP COMPETENCE OF STUDENTS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
in this article , the foreign experience of using propaganda technologies in the formation of ideological immunity , the harmony of moral qualities in the education of the youth in foreign countries, the formation of moral culture in young people, ideological propaganda, the issue of the national idea, the nation and their interdependence, the bright future of students and youth, their loyalty to their country , the effective means of developing high human qualities in determining pride are highlighted.